Analysis of Al and Cu salt infiltration into a poly 2-vinylpyridine (P2vP) polymer layer for area selective deposition applications. (3rd January 2020) - Mani-Gonzalez, P G; Snelgrove, M; Rueff, J-P; Lundy, R; Yadav, P; Bogan, J; O'Connor, R; Morris, M; Hughes, G
Abstract: This work is motivated by the desire to develop a semiconductor device patterning technology based on precursor infiltration into block copolymer materials. Developing an understanding of the preferential infiltration of metal precursors into one of the polymer blocks is of critical importance to advance this patterning approach. In this study, metal salts were used as a means to diffuse metal ions into a poly 2-vinylpyridine (P2vP) polymer brush layer ( 4 nm thick) which was deposited by spin coating on a silicon substrate. Thin P2vP films infused with aluminum nitrate and copper nitrate by a wet chemical process were analyzed with angle resolved hard x-ray photoelectron spectroscopy (AR HAXPES). From these photoemission measurements, significant information about the chemical compositional profile of the infiltrated films was obtained. The large sampling depth of HAXPES measurements (20–30 nm) enabled details of the chemical composition of the thin film to be characterized and subsequent angle-resolved HAXPES measurements offered a robust analysis of the interfaces and discrete layers that are present in the films. These measurements displayed evidence of bonding interactions between the elements in the polymer film and the infiltrated salts assisting in the development of an understanding of the infiltration process which needs to be optimized for device fabrication applications. Aluminum nitrate presented more evidence of infiltration into P2vP, while copper nitrate was more predominated at the surfaces into the P2vP.